A Critical Outlook on the Role of Research Practices in Laboratory towards Student Skills Development in Malaysian and Japanese Public Universities - Rosdi, Atiqurrahman; Azizan, Suzana Ariff; Ilham, Zul; Fujieda, Ayako; Jamil, Asyraf Isyraqi; Shaikh Mohd Saifuddeen, S.M.S; Zulkefeli, Mohd (International Journal of Innovative Research and Advanced Studies, 2020)
Developing talented graduates to fulfil market challenges is a formidable task for higher education today. By using qualitative method, Malaysian and Japanese professors in selected public universities were interviewed in order to investigate how research practices in laboratory contribute towards student skills development. The result shows that laboratory practices such as group work, mentoring and closed monitoring in organization enhance student employability skills. It is suggested that chain mentoring system from professors to junior researchers to be practiced as a succession planning in developing potential leaders. Closed monitoring between principal investigator, senior and junior researchers is also significant to support not only for professional skills, but also for personality growth and emotional support.